System, order, and international law : the early history of international legal thought from Machiavelli to Hegel - Kadelbach, Stefan, 1959-; Kleinlein, Thomas; Roth-Isigkeit, David (Oxford : Oxford University Press, 2017)
For many centuries, thinkers have tried to understand and to conceptualize political and legal order beyond the boundaries of sovereign territories. Their concepts, deeply entangled with ideas of theology, state formation, and human nature, form the bedrock of todays theoretical discourses on international law. This volume engages with models of early international legal thought from Machiavelli to Hegel before international law in the modern sense became an academic discipline of its own. The interplay of system and order serves as a leitmotiv throughout the book, helping to link historical models to contemporary discourse.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 5, 2017).
Keywords: International law -- History; Law -- Philosophy -- History; Philosophy, European -- History; Law; International law